10.24% Efficiency of Flexible Cu2ZnSn(S, Se)4 Solar Cells by Pre‐Evaporation Selenization Technique. Issue 22 (5th May 2022) - Xie, Weihao; Sun, Quanzhen; Yan, Qiong; Wu, Jionghua; Zhang, Caixia; Zheng, Qiao; Lai, Yunfeng; Deng, Hui; Cheng, Shuying
Abstract: Flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells show great potential due to non‐toxicity and low cost. The quality of CZTSSe absorber suffering from the high‐temperature selenization process is the key to overcoming open‐circuit voltage ( V OC ) deficit and obtaining high efficiency. In this work, the authors develop a selenization technique to improve the quality of the CZTSSe layer by pre‐evaporation selenization. This method provides saturated selenium vapor at the beginning of the selenization process to promote the crystallization process. The oversaturated selenium source greatly shortens the annealing time at high temperatures. The prepared CZTSSe films have larger grains and fewer voids. The measurement of the space charge limited current shows that the defect density of the CZTSSe absorber is significantly reduced from 4.43 ×  10 13  cm −3 to 3.46 × 10 13 cm −3 . Electrical tests show that the devices have better charge separation at the interface, resulting in a charge recombination lifetime, increasing from 133 to 197 µs. The power conversion efficiency of the flexible CZTSSe solar cell reaches 10.24% with V OC and the fill factor enhances to 463 mV and 62%, respectively. The safe non‐toxicity and efficient selenization method is expected to provide a new strategy for high‐efficiency flexible CZTSSe solar cells. Abstract : A feasible strategy to improve the efficiency of flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells by providing saturated selenium vapor at the beginning of annealing is proposed. The crystallinity and defects of the CZTSSe absorbers are effectively optimized. The efficiency of the fabricated flexible CZTSSe solar cells reaches 10.24%.